IMPLEMENTASI KODE ETIK GURU DALAM INTERNALISASI NILAI MORAL SISWA DI ERA DIGITAL - Abd. Mukhid; Wahyu Reynaldi Putra; Qonita Adila Siva; Alfiyatus Shofariyah; Faizatur Rahmah (STKIP Subang, 2026)
This research focuses on the application of the teacher professional code of ethics to support students' understanding of moral values ​​in the digital era. Advances in modern technology offer convenience to students' lives, but at the same time, they also pose challenges in shaping students' morals and character. Amidst the development of digital technology, teachers not only carry out educational functions but also play a strategic role as role models in instilling moral values ​​in students through the implementation of a professional code of ethics. To provide a better understanding of the subject under study, this study employed a qualitative methodology with a descriptive design. To obtain data, teachers and the Vice Principal for Public Relations at SMAN 1 Galis Pamekasan were interviewed. Documentation and relevant library sources were also included. As this research demonstrates, understanding professional ethics helps teachers become more professional. This is crucial in the process of teaching morality to students. School codes of ethics are implemented in various ways. Providing good role models, creating tangible good habits, improving student character, controlling attitudes through discipline, and incorporating ethical principles into learning activities are all examples. Various new problems arise in society amid the rapid advancement of digital technology. The increasing ease of disseminating information, the significant impact of social media on people's behavior, changes in how people interact and communicate, and the increasing likelihood of inappropriate and unethical behavior in the digital world are some of these challenges. To create students who can wisely and responsibly address the challenges of the digital age, teachers must build a strong foundation of character and personality. By using communicative and humanistic strategies, teachers also play a role in enhancing their professional abilities as educators, improving digital literacy skills, and building collaboration with schools and parents.